Vaccination Against Mycobacterial Diseases in Animals - John P. Bannantine (Frontiers Research Topics, 2015)
The two most prominent mycobacterial diseases in animals include bovine tuberculosis, caused by Mycobacterium bovis and Johne's disease, caused by Mycobacterium avium subspecies paratuberculosis. Erradication of both diseases has been hampered by a variety of factors. In many countries, the persistence of tuberculosis in cattle has been attributed to reservoirs of M. bovis in wildlife species. Brushtail possums, deer and badgers are notable examples of wildlife reservoirs for M. bovis. The difficulties in eliminating the wildlife reservoir for M. bovis further suggest the need for vaccination of farmed livestock. Vaccination of wildlife species has also been attempted with mixed results. Delivery of the vaccine to wildlife species appears to be a chief obstacle. Vaccination itself leads to complications for diagnostics. For example, when cattle are vaccinated with both BCG and a commercial Johne's vaccine there is a biased toward the avian tuberculin skin test reaction. Despite these issues, BCG seems to be the clear standard for vaccination against M. bovis, yet many laboratories are investigating ways to improve on BCG. For Johne's disease, the available commercial vaccines consist of whole-cell preparations in one form or another. But with the ability to generate directed knockouts of specific genes, a number of defined mutants have been constructed in a few laboratories. These should be tested and directly compared with each other and alongside commercial vaccine formulations to determine not only which vaccine is most protective, but which animal model is best for predicting protection in the target host. To this end, there has been a nation-wide, multi-institutional effort to test the best live, attenuated vaccine against Johne's disease in cattle, sheep and goats. This vaccine trial has spanned six years and was conducted in three phases. The first phase examined attenuation in bovine macrophages, the second phase was colonization of spleen and liver in mice and the third phase was protection from bacterial challenge in goats. Many new ideas and retrospective approaches have emerged from this unprecedented effort. These aspects will be captured in this Research Topic. In this Research Topic, we will seek articles on these above topics, but other issues surrounding vaccination of animals against mycobacteria will also be explored. These include immune parameters, correlates of protection, adjuvants and other vaccine formulations, etc.